TEACHING RUSSIAN IN VOCATIONAL SCHOOLS: PROBLEMS AND PROSPECTS (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
Teaching Russian in vocational schools plays an important role in the formation of language competencies necessary for the future professional activities of students. This article examines the main problems that arise in teaching Russian in the context of vocational education, such as the low level of student motivation, the lack of teaching materials adapted to their specialties, and the lack of qualified teachers.